2017
DOI: 10.1002/aet2.10076
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Simulation: An Experiential Learning Tool for Teaching Social Determinants of Health

Abstract: A s health care moves toward value-based care and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
(10 reference statements)
1
18
0
Order By: Relevance
“…7,13,15,29,60,77,86 Innovative simulations may provide a way to both teach and assess skills in addressing and managing SDH for health professionals. 87,88 Many of the educational interventions identified were funded through either time-limited grants or other philanthropic sources. Our findings corroborate the many known barriers to optimal teaching and learning around the SDH, specifically those of insufficient time and funding, as well as a lack of meaningful experiential learning led by expert faculty.…”
Section: Discussionmentioning
confidence: 99%
“…7,13,15,29,60,77,86 Innovative simulations may provide a way to both teach and assess skills in addressing and managing SDH for health professionals. 87,88 Many of the educational interventions identified were funded through either time-limited grants or other philanthropic sources. Our findings corroborate the many known barriers to optimal teaching and learning around the SDH, specifically those of insufficient time and funding, as well as a lack of meaningful experiential learning led by expert faculty.…”
Section: Discussionmentioning
confidence: 99%
“…To address these shortcomings, we performed a literature review to look for tools that could be used to deliver SDH training in the clinical environment. Interventions included those that did not directly relate to caseload in clinical environment [ 36 , 38 , 39 ] such as teaching kitchen approach [ 20 ], which demonstrated that experiential cooking and nutrition education improved traineesā€™ abilities to counsel patients on diet and nutrition. In addition, the review revealed a number of approaches that focused on a select cohorts of students [ 21 , 22 , 40 ā€“ 42 ].…”
Section: Steps In the Design Of A Novel Social Medicine Curriculummentioning
confidence: 99%
“…Third, simulation training is a widely established tool in medical education that can help learners experience a virtual reality through which they gain situational awareness, enhance communication skills and learn through a cycle of feedback and debriefing [23]. Simulation trainings, such as the poverty simulator which was incorporated in the Boston Medical Center MLP program described in this review [13], can be an effective experiential learning tool within SDoH training [24]. For learners who might not have previously experienced poverty, a simulator, which includes an interactive immersion experience, can sensitize participants to the ways in which their patients are constrained and shaped by economic and political forces [25].…”
Section: Discussionmentioning
confidence: 99%